Mu'jam qawa'id al-lughat al-'Arabiyah fi jadawil wa lawhat= A dictionary of Arabic grammar in charts and tables plus a repertory of conventional terms in Arabic-English-French - 175450 El-Daddah, Antoine (Beirut : Maktabah Lubnan)
PSZJBL